Effectiveness of Awareness Package on Knowledge and Attitude Regarding Prevention and Management of Elderly Health Problems among the Adults in Selected Rural Community, Bengaluru - Newar, Kalpana; Suneetha, Kala (Indian Journal of Nursing Sciences, 2024)
Background: Arthritis, hypertension, and diabetes mellitus are common diseases, which affect the elderly people over 60 years and above. Within depth-knowledge and attitude of six components of healthy ageing models such as exercise, nutrition, stress management, social support, spiritual support, and cognitive training of adults will help in maintaining healthy ageing. Aims: The aim of the study was to find the effectiveness of awareness package on knowledge and attitude and to correlate knowledge and attitude regarding prevention and management of elderly health problems among adults. Methodology: Pre-experimental one group pre-test post-test design was used. Non-probability purposive sampling technique was used to select 60 adults. Data were collected using structured knowledge questionnaire and 3 point Likert scale. Results: The mean knowledge score in pre-test was 16.03 with SD = 3.57 and the mean attitude score was 38.10 with SD = 2.79. Whereas in the post-test mean knowledge score was found 25.38 with SD = 1.99 and attitude score was 45.10 with SD = 2.46. Paired t-test shows that there was statistical significance at P < 0.0001 level. It showed there was an establishing impact of awareness package on knowledge and attitude regarding prevention and management of elderly health problems and there was significant linear correlation (r = 0.288) between knowledge and attitude regarding prevention and management of elderly health problems among the adults at P < 0.05 level. Conclusion: The study concluded that the awareness package was effective in improving level of knowledge and attitude regarding prevention and management of elderly health problems among adults